2014
DOI: 10.1016/j.jneuroim.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid sensitization of microglia in a genetic mouse model of obesity and diabetes

Abstract: db/db mice are a model of obesity and diabetes due to their lack of functional leptin receptors, which leads to insulin resistance, elevated corticosterone levels, and persistent inflammation. Because stress-induced elevations in glucocorticoids sensitize microglia to immune challenges, we hypothesized that corticosteroids might act similarly in the diabetic brain. To test this hypothesis, db/db and wildtype mice were treated with the glucocorticoid synthesis inhibitor metyrapone every day for two weeks. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 22 publications
3
51
0
Order By: Relevance
“…Microglia was highly activated in APP/PS1xdb/db mouse brain, and to a lesser extent, a similar profile was observed when astrocytes were analyzed. Our data are in agreement with recent studies (Dey et al, 2014), supporting that obesity and T2D are accompanied by central neuroinflammation, that could ultimately interfere with learning and memory processes, and it remains plausible that inflammatory conditions may contribute to observed changes in A␤ species. It has been reported that microglia may try to clear A␤ (Morgan, 2006) in order to remove amyloid pathology.…”
Section: Discussionsupporting
confidence: 93%
“…Microglia was highly activated in APP/PS1xdb/db mouse brain, and to a lesser extent, a similar profile was observed when astrocytes were analyzed. Our data are in agreement with recent studies (Dey et al, 2014), supporting that obesity and T2D are accompanied by central neuroinflammation, that could ultimately interfere with learning and memory processes, and it remains plausible that inflammatory conditions may contribute to observed changes in A␤ species. It has been reported that microglia may try to clear A␤ (Morgan, 2006) in order to remove amyloid pathology.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with other studies where it has been shown that stress can evoke a pro-inflammatory response in the brain, with increased expression of NLRP3 inflammasome involved in the cleavage and secretion of pro-inflammatory IL-1β (Gadek-Michalska et al, 2013, Frank et al, 2014). Recently, it has been shown that a stress-induced increase in corticosterone levels lowers the threshold for microglia to release pro-inflammatory cytokines (Dey et al., 2014). Increased stress has even been suggested to exacerbate neuronal cell death by increasing neuroinflammation, which in turn is neurotoxic (de Pablos et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of mice, glycemic control was assessed with intraperitoneal glucose tolerance testing, as described. 29 All of the animal procedures used in these studies were approved by the Institutional Animal Care and Use Committee of Georgia Regents University and followed the NIH Guide for the Care and Use of Laboratory Animals, and the manuscript adheres to the ARRIVE (Animal Research: Reporting in Vivo Experiments) guidelines for reporting animal experiments.…”
Section: Animals and Drug Treatmentsmentioning
confidence: 99%